On the Dependence of the Fill Factor of the Solar Module on the Temperature (Global Journal of Science Frontier Research, 2021)
The work is devoted to the conversion and use of solar energy in solar panels. The article shows that one of the clue parameters for evaluating the efficiency of solar panels and photovoltaic cells, the fill factor decreases with increasing temperature. The issue of reducing the influence of the temperature factor on the efficiency of solar panels is also considered. Based on the research, the conclusion is given that the idling voltage should be as high as possible.
Keywords: solar energy; solar battery; fill factor; temperature factor